Growth Evaluation of Selfcrossed Progenies BC1F2 Experiencing Submerged and Non-submerged at BC1F1 and its Parents - Maulidya, Azzah; Agus Suwignyo, Rujito; Susilawati; Muhardiyanto, Cahya (BIOVALENTIA: Biological Research Journal, 2024)
Abstract: A non-tidal swamp can increase rice cultivation and production, but its use is still dependent on natural conditions, making plants vulnerable to submergence and drought stress. Developing dual-tolerant varieties is essential for rice cultivation in non-tidal swamps. Inpara 8 carries the SUB1 gene, providing tolerance to submergence stress, while Inpago 5 is tolerant to drought stress. This study aimed to evaluate the growth of BC1F2 progeny from a cross between Inpara 8 and Inpago 5 under submerged stress, along with their parents (Inpago 5 and Inpara 8). The research was conducted in the greenhouse of the Agriculture Faculty at Sriwijaya University at coordinates 3°13'11.1"S 104°38'49.4"E from July 2021 to January 2022. Inpago 5 exhibited the highest average plant height (145.81 cm), the most tillers (4.73), the most productive tillers (3.87), the highest total grain per clump (720.87 grains), the heaviest clump grain weight (15.86 g), and the lowest percentage of empty grains (33.47%). The donor parent Inpara 8 had the highest average total grain per panicle (192.08) and the highest dry weight (20.69 g). BC1F2 Submerged progeny showed the highest average 1000-grain weight (25.26 g) and the fastest harvest age (114.50 DAP). The BC1F2 self-cross progeny subjected to submergence stress displayed characteristics similar to its parents, with no significant differences in observed parameters.